Authentic leadership (Boston, 2017)
What does it mean to be yourself at work? As a leader, how do you strike the right balance between vulnerability and authority? This book explains the role of authenticity in emotionally intelligent leadership. You'll learn how to discover your authentic self, when emotional responses are appropriate, how conforming to specific standards can hurt you, and when you need to feel like a fake. This volume includes the work of: Bill George Herminia Ibarra Rob Goffee Gareth Jones This collection of articles includes: "Discovering Your Authentic Leadership" by Bill George, Peter Sims, Andrew N. McLean, and Diana Mayer; "The Authenticity Paradox" by Herminia Ibarra; "What Bosses Gain by Being Vulnerable" by Emma Seppala; "Practice Tough Empathy" by Rob Goffee and Gareth Jones; "Cracking the Code That Stalls People of Color" by Sylvia Ann Hewitt; "For a Corporate Apology to Work, the CEO Should Look Sad" by Sarah Green Carmichael; and "Are Leaders Getting Too Emotional?" an interview with Gautam Mukunda and Gianpiero Petriglieri by Adi Ignatius and Sarah Green Carmichael. How to be human at work. The HBR Emotional Intelligence Series features smart, essential reading on the human side of professional life from the pages of Harvard Business Review. Each book in the series offers proven research showing how our emotions impact our work lives, practical advice for managing difficult people and situations, and inspiring essays on what it means to tend to our emotional well-being at work. Uplifting and practical, these books describe the social skills that are critical for ambitious professionals to master.
Keywords: Authenticity (Philosophy)